2013
DOI: 10.4238/2013.march.15.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IL-18 gene promoter polymorphisms on prostate cancer occurrence and prognosis in Han Chinese population

Abstract: ABSTRACT. has been implicated in a wide variety of cellular functions that affect the biological response to tumors. However, there is insufficient evidence to prove that IL-18 gene variants are associated with risk of prostate cancer. We examined a possible association between two promoter polymorphisms, -137G/C (rs187238) and -607C/A (rs1946518), in the IL-18 gene and prostate cancer occurrence and prognosis in Han Chinese. We used a high-resolution melting method to genotype these two polymorphisms in 375 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
25
0
1
Order By: Relevance
“…However, a trend of reduced cancer risk was found in genitourinary system cancer, including prostate cancer [12], [40], renal cell carcinoma [33] and bladder cancer [39]. These results suggested that the variant CA and CA/AA genotypes of IL-18 gene promoter −607 C>A polymorphism were definitive associated with cancer susceptibility, especially in nasopharyngeal carcinoma and gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, a trend of reduced cancer risk was found in genitourinary system cancer, including prostate cancer [12], [40], renal cell carcinoma [33] and bladder cancer [39]. These results suggested that the variant CA and CA/AA genotypes of IL-18 gene promoter −607 C>A polymorphism were definitive associated with cancer susceptibility, especially in nasopharyngeal carcinoma and gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 92%
“…In the study reported by Haghshenas and colleagues, the cancer types contained colorectal and stomach cancer, and the genotype frequencies were presented separately, thus each of them was considered as a separate study in this meta-analysis. A total of 23 studies for −607 C>A and 21 studies for −137G>C were finally included with 4096 cases and 5222 controls according to selection criteria[10][16], [23][40]. The detailed characteristics of the eligible studies included in this meta-analysis are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that IL-18 sequence variations are associated with several diseases, including tuberculosis, rheumatoid arthritis, Crohn's disease, Helicobacter pylori infection, ischemic stroke, hepatitis B virus (HBV)-related liver disease, hepatocellular carcinoma, and other cancers (Liu et al, 2013;Angelo et al, 2015;Bao et al, 2015a;Gao et al, 2015;Karra et al, 2015;Li et al, 2015b;Myung et al, 2015;Shi et al, 2015;Zhou et al, 2015). Zhou et al (2015) examined the association between the polymorphisms under investigation in the present study and tuberculosis, reporting that the -137G/C variant contributes to susceptibility to this disease in the Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, genetic variation in the androgen receptor has not been linked to ADT response although other hormone signaling factors appear to be related. Other candidate gene studies have focused on the vitamin D receptor [163], RNASEL [164] and IL18 [165] with mixed results.…”
Section: Pharmacogenetics Of Drugs Used To Treat Prostate Cancermentioning
confidence: 99%
“…Findings include polymorphisms in genes encoding: BNC2, TACC2, ALPK1, KIF3C, CDON, IFI30, PALLD, GABRA1, SYT9, MSMB, MYCN, PSMD7, CCL17, MON1B, CASP3, BMP5, IRS2, TRMT11, PRMT3, and HSD17B2 [165172]. Results from these studies suggest that the most important predictors of a poor response to ADT are not necessarily within androgen-related genes; however, the genetic variants identified in these studies have not been sufficiently validated from a mechanistic standpoint.…”
Section: Pharmacogenetics Of Drugs Used To Treat Prostate Cancermentioning
confidence: 99%